Induction of autophagy increases the proteolytic activity of reservosomes during Trypanosoma cruzi metacyclogenesis. Issue 2 (1st February 2021) - Losinno, Antonella Denise; Martínez, Santiago José; Labriola, Carlos Alberto; Carrillo, Carolina; Romano, Patricia Silvia
ABSTRACT: Cruzipain, the major cysteine protease of the pathogenic protozoa Trypanosoma cruzi, is an important virulence factor that plays a key role in the parasite nutrition, differentiation and host cell infection. Cruzipain is synthesized as a zymogen, matured, and delivered to reservosomes. These organelles that store proteins and lipids ingested by endocytosis undergo a dramatic decrease in number during the metacyclogenesis of T. cruzi . Autophagy is a process that digests the own cell components to supply energy under starvation or different stress situations. This pathway is important during cell growth, differentiation and death. Previously, we showed that the autophagy pathway of T. cruzi is induced during metacyclogenesis. This work aimed to evaluate the participation of macroautophagy/autophagy in the distribution and function of reservosomes and cruzipain during this process. We found that parasite starvation promotes the cruzipain delivery to reservosomes. Enhanced autophagy increases acidity and hydrolytic activity in these compartments resulting in cruzipain enzymatic activation and self- processing. Inhibition of autophagy similarly impairs cruzipain traffic and activity than protease inhibitors, whereas mutant parasites that exhibit increased basal autophagy, also display increased cruzipain processing under control conditions. Further experiments showed that autophagy induced cruzipain activation and self-processing promote T. cruzi differentiation and host cell infection. These findings highlight the key role of T. cruzi autophagy in these processes and reveal a potential new target for Chagas disease therapy. Abbreviations: Baf: bafilomycin A1 ; CTE: C-terminal extension; Cz: cruzipain; IIF: indirect immunofluorescence; K777: vinyl sulfone with specific Cz inhibitory activity; Prot Inh: broad-spectrum protease inhibitor; Spa1: spautin-1; Wort: wortmannin